2012
DOI: 10.1016/j.pediatrneurol.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Dyskinesias as a Limiting Factor in the Treatment of Segawa Disease

Abstract: Patients with autosomal dominant Segawa disease (dopa-responsive dystonia) show an excellent and sustained response to small doses of levodopa. In contrast, the development of levodopa limiting treatment dyskinesias is thought to support the diagnosis of other early onset dystonia/parkinsonism syndromes. We describe an atypical phenotype, that of persistent treatment limiting dyskinesias, in a family with prominent brachial dystonia and a novel GCH1 mutation. The pedigree comprised two affected members, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In AD-GTPCHD, most patients first received L-Dopa/DC inhibitor. Trihexyphenidyl was added due to incomplete control of symptoms on L-Dopa/DC inhibitor alone and/or due to dyskinesia at higher L-Dopa/DC inhibitor doses [141,142]. In the majority of AD-GTPCHD patients, a moderate to excellent effect on dystonia and tremor was noted; however, not all patients exhibited clinical benefit.…”
Section: Third-line Treatment Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In AD-GTPCHD, most patients first received L-Dopa/DC inhibitor. Trihexyphenidyl was added due to incomplete control of symptoms on L-Dopa/DC inhibitor alone and/or due to dyskinesia at higher L-Dopa/DC inhibitor doses [141,142]. In the majority of AD-GTPCHD patients, a moderate to excellent effect on dystonia and tremor was noted; however, not all patients exhibited clinical benefit.…”
Section: Third-line Treatment Drug Treatmentmentioning
confidence: 99%
“…There are no patients described with botulinum toxin injections as monotherapy. In one case, botulinum toxin injections were used before the diagnosis of the underlying BH 4 D. 2 other cases were concurrently treated with L-Dopa/DC inhibitor [142,148], and with trihexyphenidyl in 1 case, which did not resolve dystonic symptoms completely (writer's cramp, blepharospasm, and retrocollis). All patients improved with botulinum toxin injections; however, the co-administration of other medications does not permit evaluation of the effect of botulinum toxin alone.…”
Section: Other Supportive Therapiesmentioning
confidence: 99%
“…107 When levodopa-induced dyskinesia does occur, it usually presents at the initiation of treatment and is the result of unusually high doses. 19,25,35,[111][112][113] As in patients with PD, amantadine can suppress levodopa-induced dyskinesia in GTP-CH-I deficiency. 114 The available evidence indicates that levodopa can be used safely during pregnancy to treat GTP-CH-I deficiency, as studies that included treatment of pregnant patients reported no fetal abnormalities.…”
Section: Treatmentmentioning
confidence: 99%
“…later slow increment in dose [14,15]. However, it is known, that some GCH1 mutations like in frame deletion in exon 1 c.235_240delCTGAGC/p.Leu79_Ser80del cause persistent treatment limiting dyskinesias, which may develop after few years of continuous L-dopa therapy [16]. Some patients may also present with DRD showing atypical symptoms such as hand tremor, spastic paraplegia, rigidity [11,12,15].…”
Section: Discussionmentioning
confidence: 99%